OPTIMALISASI TRANSFER OF RESPONSIBILITY CONTROL ANTARA PANGKALAN BUN APPROACH DENGAN BANJARMASIN FLIGHT SERVICE STATION - Yunita Qurnia Wasistha; Wasito Utomo; Siti Nurfadhilah (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Transfer of responsibility control between Pangkalan Bun Approach and Banjarmasin Flight Service Station is not optimal for aircraft flying at altitudes below 4000 feet. Due to the radio communication range between the aircraft and the Banjarmasin FSS unit. The problem formulation of this research is "What is the responsibility of air space from the movement of aircraft in the Pangkalan Bun Control Zone (CTR) to the Banjarmasin FSS airspace?". This study aims to find out the procedures for air traffic services in the Pangkalan Bun TMA area in accordance with existing procedures and to optimize the facilities of related units to be better to support security and safety in air traffic services. The research method used in writing uses a qualitative descriptive method. The population in this study were all personnel of the Air Traffic Controller Office of Perum LPPNPI Sub-Branch of Pangkalan Bun. Data collection techniques used are observation, interviews, and questionnaires. Based on the data and the results of the discussion, it can be concluded that the range owned by the Banjarmasin FSS unit is a factor that causes aircraft with a cruising altitude below 4000 feet to be unable to carry out two-way communication.